Populasi Bakteri, Fungi, dan Biomassa Karbon Mikroba pada Agroforestri dan Monokultur Kakao - Zulkaidhah Zulkaidhah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Land-use simplification may alter soil biological quality by reducing vegetation diversity, organic matter inputs, and habitat availability for soil microorganisms. This study aimed to analyze soil bacterial populations, fungal populations, and microbial biomass carbon under complex agroforestry, simple agroforestry, and cocoa monoculture systems around Lore Lindu National Park, Central Sulawesi. Soil samples were systematically collected from five sampling points within each land-use system at a depth of 0–20 cm. Culturable bacterial and fungal populations were determined using serial dilution and total plate count methods, while microbial biomass carbon was measured using chloroform fumigation extraction. Data were analyzed using one-way analysis of variance followed by the Least Significant Difference test at the 5% significance level. Land-use type significantly affected all measured biological parameters. Complex agroforestry produced the highest bacterial population, fungal population, and microbial biomass carbon, reaching 9.08 × 10⁸ CFU g⁻¹, 6.84 × 10⁵ CFU g⁻¹, and 822.80 mg C kg⁻¹, respectively. Simple agroforestry showed intermediate values, whereas cocoa monoculture produced the lowest values. These findings demonstrate that greater vegetation complexity supports soil microbial abundance and biomass by providing diverse organic substrates and more stable microenvironmental conditions. Maintaining shade-tree diversity in cocoa agroforestry is therefore important for conserving soil biological quality in the buffer zone of Lore Lindu National Park.